Sovereign credit spreads under good/bad governance - Jeanneret, Alexandre (Journal of Banking & Finance, 2018)
This paper explores how sovereign credit spreads vary with the level of governance. An analysis of 74 countries over the 2001–2016 period shows that sovereign credit default swap (CDS) spreads decrease with government effectiveness, particularly in countries exhibiting severe default risk, high indebtedness, and poor economic conditions. We formulate a theoretical explanation for these findings using a structural model in which governments adjust default and debt policies based on their abilities to collect and use fiscal revenues. The theory posits that more effective governments have less incentive to default and thus benefit from narrower credit spreads, although they may choose higher indebtedness levels.